1988
DOI: 10.1523/jneurosci.08-02-00564.1988
|View full text |Cite
|
Sign up to set email alerts
|

A developmentally regulated antigen associated with neural cell and process migration

Abstract: The distribution of an epitope recognized by the monoclonal antibody JONES has been studied immunohistochemically in the developing nervous system of the rat. In the present report, we survey selected regions of the fetal, postnatal, and adult rat nervous system to test the hypothesis that JONES binding is invariably associated with neural cell migration and axon growth in the developing rat. A series of selected developmental stages extending from embryonic day (E) 9 to adult were used in this investigation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…The selection of antibodies for analysis has generally been based on the ability of the antibody to interfere with a predetermined function such as cell adhesion (Edelman, 1983;Kruse et al, 1985) or an immunolabeling pattern that indicates developmental regulation (Mendez-Otero et al, 1988). We have used the latter method to produce a monoclonal antibody (2A1) that recognizes an antigen expressed on the surface of neurons of the central nervous system of the mouse.…”
mentioning
confidence: 99%
“…The selection of antibodies for analysis has generally been based on the ability of the antibody to interfere with a predetermined function such as cell adhesion (Edelman, 1983;Kruse et al, 1985) or an immunolabeling pattern that indicates developmental regulation (Mendez-Otero et al, 1988). We have used the latter method to produce a monoclonal antibody (2A1) that recognizes an antigen expressed on the surface of neurons of the central nervous system of the mouse.…”
mentioning
confidence: 99%
“…We have investigated the possible role of 9-O-acetyl GD3 in the glial-guided neuronal migration using the developing rat cerebellum as a model. In previous studies we had shown that the expression of this ganglioside is developmentally regulated in the developing cerebellum (28). In E14-18 fetuses, immunocytochemistry labeling with Jones mAb is present, extending from the ventricular to the pial surface of the cerebellar anlage.…”
Section: Gangliosides In Glial-guided Radial Migrationmentioning
confidence: 82%
“…In our initial studies we have shown that the pattern of staining with this antibody in the developing rat nervous system correlates temporally and spatially with neuronal migration and neurite outgrowth (28,29). The biochemical characterization of the antigen revealed that this mAb recognizes a ganglioside that migrates between GM1 and GM2 ganglioside standards.…”
Section: Gangliosides and Neuronal Motilitymentioning
confidence: 96%
See 2 more Smart Citations